The Cost of Orthodoxy - Cameron, Averil (Church history and religious culture, 2013)
The quest for orthodoxy began in the earliest days of Christianity, and has continued unabated until today, after two thousand years of church councils and theological argument. In the western church, the Council of Chalcedon (ad451) is generally taken to be a watershed, or even to have settled the most important questions. This was not the case in the east, where Chalcedon was immediately questioned, leading to the separation of the eastern churches. Byzantinists tend to suppose that the ending of iconoclasm in ad843 characterised the nature of Byzantine orthodoxy for the future. This paper argues that ‘orthodoxy’ was always fluid, and that its definition, and still more its imposition, were always fought over, and required constant effort, energy and an outpouring of oral and written argument. This effort was costly for institutions and individuals alike, and was far less successful than it seems.